TREATMENT COMPLIANCE AND BLOOD SUGAR LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Mardaningrat, Gede Ari Mahendra; Parining, Ketut; Utami, Made Aristia (E-Jurnal Medika Udayana, 2025)
Achieving acceptable levels of glycemic control to avoid short- and long-term complications requires comprehensive management of diabetes mellitus (DM), including medical, dietary, and lifestyle modifications. DM has become one of the most common chronic diseases worldwide. The relationship between blood glucose levels and medication adherence in patients with type II DM at the Seririt I Health Center was sought to be determined in this study. This research included an analytical study conducted at the Seririt I Health Center from June 2023 to August 2023. This study used a cross-sectional design where the number of samples was used a total of 75 people were taken using a sampling technique, namely total sampling. Data were collected by interviewing patients, viewing patient medical records, and conducting blood sugar checks. The research data were summarized in Microsoft Excel and then analyzed with SPSS 16.0 for descriptive statistics. The results of the study showed that at the Seririt I Health Center, the highest number of patients with DM were found in the female group (64%), the age group > 60 years (49.4%), DM from Patemon (25.3%), and DM sufferers accompanied by comorbid hypertension (53.3%), DM treatment with metformin and glibenclamide (44%). The study's results also showed that DM patients had a relatively good level of treatment compliance (82.7%), and normal blood sugar levels (77.3%). In this study, a correlation test was also carried out, and significant results were obtained (p < 0.05) between treatment compliance and blood sugar levels in type 2 DM patients. One effort to control blood glucose or prevent complications caused by DM is to implement treatment compliance behaviour for DM sufferers.